PERAN KEPUASAN PELANGGAN DALAM MEMEDIASI PENGARUH EXPERIENTAL MARKETING DAN KUALITAS LAYANAN TERHADAP NIAT BELI ULANG PEMBELIAN TIKET PESAWAT (STUDI PADA PT AGENI TOUR & TRAVEL SEMARANG) - Andhiani Kameshwara, 14.05.51.0010 (Students' Journal of Economic and Management, 2019)
This study aims to analyze the role of customer satisfaction in mediating the influence of experiential marketing and service quality on repurchase intentions. This research was conducted at PT. Ageni Tour & Travel Semarang. This study uses descriptive research. The number of samples is 100 respondents. The research instrument used a questionnaire. Data analysis used multiple regression analysis and mediation test. The results of the study show that the role of customer satisfaction in mediating the influence of experiential marketing and service quality is positive and significant towards repurchase intention. While the results of mediation test positive and significant marketing experiential influence on customer satisfaction.